The Isolation and Molecular Characterization of an Astrovirus From “Yellow” Chickens, China - Zhao, Wei; Wu, Zongyi; Yao, Yongxiu; Qin, Aijian; Qian, Kun (Frontiers in Veterinary Science, 2020)
Chicken astrovirus (CAstV) infection is strongly associated with kidney disease, gout, “white chicks” hatchery disease and runting and stunting syndrome (RSS). In the present study, 82.5% of 154 clinical samples from different provinces in China were positive for CAstV by RT-PCR. One CAstV isolate, designated as AAstV/Chicken/CHN/2017/NJ01, was successfully isolated from the small intestine of "Yellow" chickens using LMH cells. The genomic sequence and structural analyses revealed that NJ1701 had the typical characteristics of avian astroviruses which was genetically distinct from other Avsatrovirus. This isolate was classified as Group B subgroup i based on phylogenetic analysis of complete ORF 2 (capsid) amino acid sequences. Meanwhile, growth depression and hatchability reduction were observed in the chicken embryos infection experiment. The results in current study will contribute to our understanding of Chicken astrovirus in China and provide one virus strain that may serve as candidate vaccine.